2017
DOI: 10.1007/s10729-017-9399-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient choice modelling: how do patients choose their hospitals?

Abstract: As an aid to predicting future hospital admissions, we compare use of the Multinomial Logit and the Utility Maximising Nested Logit models to describe how patients choose their hospitals. The models are fitted to real data from Derbyshire, United Kingdom, which lists the postcodes of more than 200,000 admissions to six different local hospitals. Both elective and emergency admissions are analysed for this mixed urban/rural area. For characteristics that may affect a patient's choice of hospital, we consider th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 39 publications
1
48
0
1
Order By: Relevance
“…8 It is unknown to what extent patients consider religious affiliation when selecting their health care facilities and whether they believe institutions have the right of conscience over their own medical desires and needs. Prior surveys [9][10][11][12][13] of factors that patients consider when choosing health care facilities have demonstrated that financial factors, travel distance and time, and hospital size were most important; none specifically inquired about religious affiliation. Given the growing religious health care sector in the United States, we set out to better understand how US patients perceive religious affiliations of health care organizations.…”
Section: And 46mentioning
confidence: 99%
See 1 more Smart Citation
“…8 It is unknown to what extent patients consider religious affiliation when selecting their health care facilities and whether they believe institutions have the right of conscience over their own medical desires and needs. Prior surveys [9][10][11][12][13] of factors that patients consider when choosing health care facilities have demonstrated that financial factors, travel distance and time, and hospital size were most important; none specifically inquired about religious affiliation. Given the growing religious health care sector in the United States, we set out to better understand how US patients perceive religious affiliations of health care organizations.…”
Section: And 46mentioning
confidence: 99%
“…16 We focused survey development on understanding patient views of religious institutional health care. Our survey was informed by prior surveys, [9][10][11][12][13] and questions were added or modified to extend queries related to religious institutional health care affiliations. We used expert panel review and piloted the preliminary draft with 5 lay individuals to ensure readability and absence of ambiguity.…”
Section: Jama Network Open | Public Healthmentioning
confidence: 99%
“…proximity, size, and teaching hospital status), and other factors unrelated to surgical performance. 19,20 On the other hand, steps have been taken to reduce the risk of surgeons avoiding difficult cases in specialties where it was feared this was an issue, 21 and recent evidence suggests that surgical behaviour is no more risk averse since publication of surgeon-specific mortality data in colorectal surgery. 22 However, and perhaps more pertinent to LMICs, there is evidence that the behaviour of staff throughout the multidisciplinary team might be affected by the perception that measurement is about performance management.…”
Section: Challenges In Implementationmentioning
confidence: 99%
“…23 In lowand middle-income settings, the hierarchical structure of healthcare, with dominance of doctorsdand particularly surgeonsdover other health professionals, can exaggerate these problems, and lead to inaccurate documentation and lack of reporting of real problems. 20,24 If hospitals and healthcare professionals think they are being judged, they may deliberately or accidentally manipulate their data in order to look better, avoid reprisal, and therefore save their jobs and their reputations. This is true of all healthcare settings, but likely to be more of a problem in settings that are plagued by corruption and a 'blame' culture, both of which, regrettably, are more likely in LMICs.…”
Section: Challenges In Implementationmentioning
confidence: 99%
“…We use the choice of health facilities to measure it in this study. International studies compared patients’ choice of particular hospitals with adjusting characteristics of hospitals (size or capability of service),18 19 while few divided health facilities into primary healthcare facilities, private and public hospitals 20. Studies on choice of health facilities in China divided health facilities into different levels 21 22…”
Section: Introductionmentioning
confidence: 99%